Factors of College Involvement and Belonging for First-Generation Students of Color. Issue 1 (2nd January 2023) - Thornhill, Carly W.; Wied, Caroline M.; Spooner, Mikaela M. N.; Terrazas, Aileen; Evans, Tyler S.
ABSTRACT: This study uses data from the Healthy Minds Study national dataset of first-generation college students of color (N = 853) to examine the relationship between students' sense of belonging and college involvement factors such as extracurricular activities, diversity exposure, residence, and academic impairment. Results from the hierarchical multiple regression (HMR) model predicted 18.9% of the variability in sense of belonging. The model showed a statistically significant association between sense of belonging and the college involvement factors of academic impairment, campus diversity, and extracurricular involvement. Implications for first-generation college students of color and institutions will be discussed.